Dual‐Crosslinked Dynamic Hydrogel Incorporating Mo154 with pH and NIR Responsiveness for Chemo‐Photothermal Therapy (Adv. Mater. 40/2021). Issue 40 (5th October 2021) - Guedes, Gabriela; Wang, Shiqi; Fontana, Flavia; Figueiredo, Patrícia; Lindén, Jere; Correia, Alexandra; Pinto, Ricardo J. B.; Hietala, Sami; Sousa, Filipa L.; Santos, Hélder A.
Abstract : Photothermal Materials In article number 2007761, Shiqi Wang, Hélder Santos, and co‐workers introduce a polyoxometalate Mo154 ‐incorporating, dual‐crosslinked dynamic hydrogel (Mo154 Gel) formed by Schiff base and electrostatic interactions. Mo154 Gel shows exceptional photothermal conversion, and pH‐ and near‐infrared‐laser‐triggered drug release. This work paves the way for the development of novel Mo154 ‐based platforms incorporated in self‐healing and injectable hydrogels for combinatorial chemo‐photothermal cancer therapy.